Panel-Oriented Surrogate Model for Developing Class Fragility Curves for Transmission Towers - Wang, Xinyue; ICASP14; Ma, Liyang; Bocchini, Paolo (My University, 2023)
A panel-oriented surrogate model for classes (or portfolios) of transmission towers is presented. The surrogate model can be implemented as a beam-column element, whose validity is established through rigorous abstraction of the load cases and panel behaviors. The force-engineering demand parameter (EDP) curves for different load cases are derived using a high-fidelity finite element model of the panel. The results confirm that distinct load paths and member groups dictate the panel’s behaviors under different load cases. While the leg buckling drives the panel’s failure under compressive and bending load cases, the joint slippage and joint failure control the panel’s failure under shear and torsion load cases. The modeling parameters of the surrogate model are calibrated with a focus on the axial and transverse deformations. The exhaustive search method is used for calibration. The simple beam-column element implementation can significantly reduce the cost of model building and analysis of transmission towers, which is particularly useful for developing class fragility models to support the regional portfolio analysis of transmission systems.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED